GREEN ENERGY DIVERSIFICATION AND FINANCIAL PERFORMANCE OF INDONESIAN COAL MINING COMPANIES - Sulestiowidagdo, Ignatius Dwi; Nainggolan, Yunieta Anny (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Darma Agung (LPPM_UDA), 2024)
Currently, coal is one of the most widely used fuels in power generation in Indonesia. However, with the Indonesian government's desire to achieve net zero emissions by 2060, coal companies are challenged to maintain their businesses by that time. Some coal mining companies have started diversifying their businesses by investing in the green energy sector. This study aims to investigate the relationship between business diversification of coal mining companies into the green energy sector and the relation with the financial performance of coal mining companies using the indicators ROA (Return on assets), Tobin’s Q, and ROIC (Return on Invested Capital). The study examines all listed coal mining companies that have diversified into green energy businesses from 2018 to 2022. The panel data regression results show that business diversification into green energy has a positive and significant effect on improving the financial performance of coal mining companies in terms of ROA, Tobin’s Q, and ROIC.